Формирование пространства признаков для распознавания аномалий сетевого трафика с использованием методов мультифрактального анализа - Дидык, А.А. (Міжнародний науково-навчальний центр інформаційних технологій і систем НАН та МОН України, 2009)
Usage of multifractal formalism for analysis of network traffic structure for the purpose of anomalies revealing are considered in this paper. Multifractal spectrums of normal and abnormal (with presence of some sorts of network attacks) traffics are presented. It s shown, that multifractal spectrums of two sorts of traffic considerably differ and that gives possibility to detect in due time abnormal activity in computer systems.